2006
DOI: 10.1021/es052580b
|View full text |Cite
|
Sign up to set email alerts
|

Biological Monitoring of Polyfluoroalkyl Substances:  A Review

Abstract: Polyfluoroalkyl substances (PFSs) are used in industrial and commercial products and can degrade to persistent perfluorocarboxylates (PFCAs) and perfluoroalkyl sulfonates (PFSAs). Temporal trend studies using human, fish, bird, and marine mammal samples indicate that exposure to PFSs has increased significantly over the past 15-25 years. This review summarizes the biological monitoring of PFCAs, PFSAs, and related PFSs in wildlife and humans, compares concentrations and contamination profiles among species and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
781
5
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,132 publications
(814 citation statements)
references
References 78 publications
26
781
5
2
Order By: Relevance
“…Interestingly, the concentration profile of PFOS and PFNA in Baikal seal liver was unique; the mean ((SD) concentration ratio of PFNA to PFOS in individual seals was 1.7 ( 6.3. In contrast to the predominance of PFNA in Baikal seal, PFOS has been found previously to be the most abundant PFC in most wildlife species from various locations (28). A previous study showed that the concentrations of PFNA (mean 16 ng/g) were approximately 2-fold greater than those of PFOS (mean 8.7 ng/g) in the liver of mink (Mustela vison) collected from Watson Lake, Yukon (7).…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, the concentration profile of PFOS and PFNA in Baikal seal liver was unique; the mean ((SD) concentration ratio of PFNA to PFOS in individual seals was 1.7 ( 6.3. In contrast to the predominance of PFNA in Baikal seal, PFOS has been found previously to be the most abundant PFC in most wildlife species from various locations (28). A previous study showed that the concentrations of PFNA (mean 16 ng/g) were approximately 2-fold greater than those of PFOS (mean 8.7 ng/g) in the liver of mink (Mustela vison) collected from Watson Lake, Yukon (7).…”
Section: Resultsmentioning
confidence: 92%
“…Perfluorooctanoic acid was not detected in most sea turtle species from most locations, however, it is a common PFC measured in human plasma [3] and is frequently detected in fish and marine mammals [3], but most often at concentrations lower than PFOS. The lack of PFOA in most turtles suggests that they are either less exposed to this compound or they have an efficient pathway to eliminate this compound from their blood.…”
Section: Discussionmentioning
confidence: 91%
“…The most studied and commonly detected PFCs in the environment are perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA). These substances have been detected in human and wildlife samples worldwide, including several species of seabirds and marine mammals [3,4] and have been shown to biomagnify in various food webs [4][5][6]. Two studies have previously reported PFCs in sea turtle samples, with interesting contrasts between species, as well as geographical and temporal differences in PFC concentrations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Categories of chemicals that have a greater tendency to be ionogenic include surfactants (anionic and cationic), pharmaceuticals (predominantly bases), and some classes of pesticides (e.g., systemic herbicides and fungicides) [1][2][3]. Perfluoroalkyl acids (PFAAs) such as perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) are among the most widely known group of ionogenic organic chemicals (IOCs) due to public health concerns and the research effort dedicated to understanding the fate, transport, and bioaccumulation potential of these compounds over the past decade [4][5][6]. Environmental risk assessment of pharmaceuticals has also become an increasingly important issue from both a research and a regulatory perspective [7,8].…”
Section: Introductionmentioning
confidence: 99%